Electromechanical and systems engineering : selected, peer reviewed papers from the 5th International Congress of Electromechanical and Systems Engineering, 10th-14th November 2008, National Polytechnic Institute, Mexico City - Urriolagoitia C., Guillermo (Urriolagoitia Calderón); Hernández-Gómez, L. H. (Luis Hector); Toledo-Velázquez, M. (Miguel) (Applied mechanics and materials ;, 2009)
This volume presents selected peer-reviewed papers related to diverse aspects of mechanics and materials. Cases related to the flow of fluids under various conditions, as well as heat transfer, are analyzed. There are also contributions, to the field of the design of mechanisms, which focus on biomechanics and the synthesis of mechanisms. Papers on mechanical vibration are linked to the design of machine tools, rotodynamics and vibrations in microbeams. Also, the evaluation of residual stresses and the estimation of the mechanical properties of vegetal materials are treated. Finally, fractal analysis is applied to solar radiation, and to the materials used in nanomedicine. The 21 papers are grouped into: Fluid Mechanics, Heat Transfer, Biomechanics and Design of Mechanisms, Mechanical Vibrations, Testing Materials, Fractal Analysis and Numerical Analysis. The result is an intriguing and eclectic guide to some fields of rapidly growing importance.